A method for preparing lithium-rich manganese-based positive electrode material

The lithium-manganese-based positive electrode material is prepared through the co-precipitation-sand grinding-spray drying process, which solves the problem that it is difficult to achieve high tap density while having high capacity and high cycling performance, and achieves efficient preparation and performance improvement of the material.

CN118954633BActive Publication Date: 2025-02-28HANGZHOU XIGU TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411449458.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-28
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

Lithium-rich manganese-based positive electrode materials are difficult to achieve high tap density while having high capacity and high cycle performance, which hinders its commercial application.

Method used

The nickel-cobalt source was prepared by co-precipitation reaction, and mixed with manganese source, lithium source, carbon source and water to sand mill, followed by spray drying, and finally obtained a lithium-rich manganese-based positive electrode material by pre-sintering and sintering.

Benefits of technology

The high capacity, high circulation performance and high tap density of lithium-rich manganese-based cathode material have been achieved, which has enhanced its application prospects in lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118954633B_ABST
    Figure CN118954633B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a lithium-rich manganese-based positive electrode material, comprising the following steps: coprecipitating a nickel-cobalt mixed salt solution, a precipitant and a complexing agent to obtain a nickel-cobalt source; mixing the nickel-cobalt source, manganese source, lithium source, carbon source and water, sand milling to obtain a sand milling slurry; spray drying the sand milling slurry to obtain a precursor; pre-calcining and sintering the precursor to obtain a lithium-rich manganese-based positive electrode material. The lithium-rich manganese-based positive electrode material prepared under the innovative process of coprecipitation-sand milling-spraying and the introduction of a carbon source has a high tap density, high capacity and high cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of positive electrode material preparation, and in particular relates to a method for preparing a lithium-rich manganese-based positive electrode material. Background Art

[0002] Lithium-ion batteries have the advantages of high operating voltage, high specific energy, long cycle life, and environmental protection. They are the most promising energy storage devices so far and are widely used in digital products and electric vehicles. The current mainstream positive electrode materials are lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4) and nickel cobalt manganese ternary positive electrode materials (LiNi 1-x-y Mn x Co y O2, NCM) and lithium nickel cobalt aluminum oxide (LiNi 1-x-y Al x Co y O2, NCA) and other layered cathode materials have a relatively mature development, however, these traditional cathode materials show obvious bottlenecks in the face of high capacity. Lithium-rich manganese gene has the characteristics of ultra-high reversible cycle specific capacity (>250mAh / g), high operating voltage (>3.8V), low production cost and environmental friendliness. It is one of the cathode materials with the most research value and application prospects in high-capacity lithium-ion secondary batteries.

[0003] Lithium-rich manganese-based positive electrode materials have disadvantages such as poor rate performance, capacity attenuation and low tap density, which hinder the commercial application of this material. Current research mainly focuses on the in-depth exploration of the internal structure of lithium-rich manganese-based materials and the modification of the materials such as doping, coating, surface modification, etc. However, in most cases the performance of the materials still needs to be improved and the high cost of preparation makes it difficult to achieve industrialization. It is also difficult to ensure that the lithium-rich manganese-based positive electrode materials have high tap density while having high capacity and high cycle performance. Summary of the invention

[0004] In view of this, an object of the present invention is to provide a method for preparing a lithium-rich manganese-based positive electrode material, wherein the positive electrode material prepared by the method has high capacity, high cycle performance and high tap density.

[0005] The present invention provides a method for preparing a lithium-rich manganese-based positive electrode material, comprising the following steps:

[0006] The nickel-cobalt mixed salt solution, the precipitant and the complexing agent are subjected to co-precipitation reaction to obtain a nickel-cobalt source;

[0007] The nickel-cobalt source, manganese source, lithium source, carbon source and water are mixed and sand-milled to obtain sand-milled slurry;

[0008] spray drying the sand-milled slurry to obtain a precursor;

[0009] The precursor is pre-sintered and sintered to obtain a lithium-rich manganese-based positive electrode material.

[0010] The present invention prepares a nickel-cobalt source by coprecipitation, then adds raw materials such as a carbon source, performs sand grinding, and spray-dries the obtained lithium-rich manganese-based positive electrode material to have high capacity, high cycle performance, and high tap density.

[0011] The present invention performs a coprecipitation reaction on a nickel-cobalt mixed salt solution, a precipitant and a complexing agent to obtain a nickel-cobalt source. The present invention mixes a nickel salt, a cobalt salt and deionized water, and fully stirs to obtain a nickel-cobalt mixed salt solution. The salt in the nickel-cobalt mixed salt solution is selected from one or more of sulfate, nitrate and acetate; the molar ratio of nickel to cobalt is 1:0.7-1.4; the concentration of nickel ions in the nickel-cobalt mixed salt solution is 1-2 mol / L; the concentration of cobalt ions in the nickel-cobalt mixed salt solution is 1-2 mol / L.

[0012] The precipitant used in the present invention is sodium hydroxide solution or sodium carbonate solution; the concentration of the precipitant is 0.1~2 mol / L. The complexing agent is selected from ammonia water or NH4·HCO3. The temperature of the coprecipitation reaction is 40~70°C, and the reaction is stopped when the target particle size D50 is reached. The present invention synthesizes a nickel-cobalt source with a smaller particle size through a coprecipitation synthesis method to ensure that it is fully ground during the sand milling process, and the particle size D50 of the nickel-cobalt source is 3~20 microns. The nickel-cobalt source is a hydroxide or a carbonate, and has a low phase change temperature, which makes it easier for nickel, cobalt, manganese, and lithium elements to combine into a structurally stable lithium-manganese-rich phase during the sintering process, thereby improving the capacity and cycle performance of the positive electrode material. In a specific embodiment, the nickel-cobalt source is Ni 1 / 2 Co 1 / 2 (OH)2 precursor or Ni 1 / 2 Co 1 / 2 CO3 precursor.

[0013] After obtaining the nickel-cobalt source, the present invention mixes the nickel-cobalt source, manganese source, lithium source, carbon source and water, and sand grinds to obtain sand grinding slurry. The manganese source is selected from one or more of manganese dioxide, dimanganese trioxide and trimanganese tetraoxide; the lithium source is selected from one or more of lithium hydroxide, lithium carbonate, lithium acetate and lithium nitrate. The total solid content of the sand grinding slurry is 5-50%, wherein the solid content is the sum of the nickel-cobalt source and / or the manganese source.

[0014] The carbon source used in the present invention is selected from one or more of glucose, sucrose, starch, CMC and polyethylene glycol; the concentration of the carbon source in the sand-grinding slurry is 0.01-0.8 mol / L. The above specific types of carbon sources can appropriately increase the viscosity of the slurry and the surface tension of the spray droplets, thereby increasing the solidity of the particles and further increasing the tap density.

[0015] The pH value of the sand-milling slurry in the present invention is 8.6-13, the sand-milling temperature is 40-60° C., the sand-milling time is 0.5-24 hours, and the sand-milling speed is 1000-3000 rpm. The present invention sand-mills in a sand mill.

[0016] After obtaining the sand-milled slurry, the present invention spray-dries the sand-milled slurry to obtain a precursor. The inlet air temperature of the spray drying is 150-500°C, the outlet air temperature is 80-150°C, and the peristaltic pump speed is 15-25rpm. After the slurry is spray-dried by the sprayer, a solid sphere with a D50 size of 4-20 microns and a narrow particle size distribution is formed, that is, the granulation process of the secondary particles is completed, so that the final product has more uniform and stable electrochemical properties. In a specific embodiment, the inlet air temperature of the spray drying is 250°C or 240°C or 220°C; the outlet air temperature is 125°C or 118°C or 115°C; the peristaltic pump speed is 20 rpm; and the D50 of the precursor is 8.5 microns or 10.5 microns.

[0017] After obtaining the precursor, the present invention pre-sinters and sinters the precursor to obtain a lithium-rich manganese-based positive electrode material. The pre-sintering temperature is 450-700°C, the heating rate is 1-20°C / min, and the heat preservation time is 0.5-24h; the sintering temperature is 750-1100°C, the heating rate is 1-20°C / min, and the heat preservation time is 0.5-24h.

[0018] The composition of the lithium-rich manganese-based positive electrode material prepared by the present invention is Li x Ni y Co z Mn t O2, wherein x is 0.9-1.4, y is 0.11-0.29, z is 0.11-0.29, and t is 0.51-0.58. In a specific embodiment, the composition of the lithium-rich manganese-based positive electrode material is Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

[0019] Figure 1 Schematic diagram of the preparation process of the lithium-rich manganese-based positive electrode material of the present invention; Figure 1 It can be seen that Ni, Co sources, precipitant and complexing agent are mixed and co-precipitated to obtain a precipitate; the precipitate is washed and dried to obtain a nickel-cobalt source; the Ni-Co source is mixed with a lithium source and a Mn source and then sand-milled, the collected slurry is spray-dried, and the collected powder is sintered to obtain a lithium-rich manganese-based positive electrode material.

[0020] The present invention provides a method for preparing a lithium-rich manganese-based positive electrode material, comprising the following steps: co-precipitating a nickel-cobalt mixed salt solution, a precipitant and a complexing agent to obtain a nickel-cobalt source; mixing the nickel-cobalt source, manganese source, lithium source, carbon source and water, sand-milling to obtain a sand-milled slurry; spray-drying the sand-milled slurry to obtain a precursor; pre-calcining and sintering the precursor to obtain a lithium-rich manganese-based positive electrode material. The lithium-rich manganese-based positive electrode material prepared by the above process has a high tap density, high capacity and high cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic diagram of the preparation process of the lithium-rich manganese-based positive electrode material of the present invention;

[0022] Figure 2 This is a SEM image of the lithium-rich manganese-based positive electrode material prepared in Example 1 of the present invention;

[0023] Figure 3 This is a SEM image of the lithium-rich manganese-based positive electrode material prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0024] In order to further illustrate the present invention, a method for preparing a lithium-rich manganese-based positive electrode material provided by the present invention is described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.

[0025] Example 1

[0026] (1) Weigh a certain amount of NH3·H2O as a complexing agent, NaOH as a precipitant, CoSO4·7H2O and NiSO4·6H2O mixture (molar ratio of 1:1) and dissolve them in pure water (concentrations of 0.6 mol L -1 , 1.5 mol L -1 , 2 molL -1 ), and then pumped into a continuous stirred tank reactor under nitrogen protection and stirring conditions. During the process, the temperature was maintained at 60°C, the pH value was maintained at 11.5, and the rotation speed was 350 rpm. After the reaction, the material was collected, filtered, washed, and dried to obtain Ni with a particle size D50 of 8.5 microns. 1 / 2 Co 1 / 2 (OH)2 precursor;

[0027] (2) 39.561 g of the precursor obtained in step (1), 80 g of MnO2, and 79.81 g of LiOH·H2O were taken, 2 L of pure water was used as a medium, and 28 g of sucrose was added into a sand mill for sand grinding to obtain a slurry;

[0028] (3) adding the slurry obtained in step (2) into a spray dryer through a peristaltic pump for spray drying, wherein the inlet air temperature of the spray drying is 250°C, the outlet air temperature is 125°C, and the peristaltic pump speed is 20 rpm to obtain a solid powder;

[0029] (4) The powder of step (3) is placed in a box furnace for pre-sintering and sintering. In the first step, the temperature is raised to 600 ° C and kept at this temperature for 6 h, and the heating time is 140 min; in the second step, the temperature is raised to 900 ° C and kept at this temperature for 6 h, and the heating time is 180 min to obtain a high-performance lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

[0030] Example 2

[0031] (1) Weigh a certain amount of NH4·HCO3 as a complexing agent, Na2CO3 as a precipitant, CoSO4·7H2O and NiSO4·6H2O mixture (molar ratio of 1:1) and dissolve them in pure water (concentrations of 0.25 mol L -1 , 2 mol L -1 , 2 mol L -1 ), and then pumped into a continuous stirred tank reactor under nitrogen protection and stirring conditions. During the process, the temperature was maintained at 60 ° C, the pH value was maintained at 8.6, and the rotation speed was 400 rpm. After the reaction, the material was collected and filtered, washed, and dried to obtain Ni with a particle size D50 of 10.5 microns 1 / 2 Co 1 / 2 CO3 precursor;

[0032] (2) taking 52.638 g of the precursor obtained in step (1), weighing 80 g of MnO2 and 79.81 g of LiOH·H2O, adding 2 L of pure water as a medium and 14 g of sucrose, and putting them into a sand mill for sand grinding to obtain a slurry;

[0033] (3) adding the slurry obtained in step (2) into a spray dryer through a peristaltic pump for spray drying, wherein the inlet air temperature of the spray drying is 240°C, the outlet air temperature is 118°C, and the peristaltic pump speed is 20 rpm to obtain a solid powder of uniformly mixed elements;

[0034] (4) The powder of step (3) is placed in a box furnace for a two-stage calcination process. In the first step, the temperature is raised to 600°C and kept at this temperature for 3 h, and the heating time is 140 min; in the second step, the temperature is raised to 900°C and kept at this temperature for 10 h, and the heating time is 180 min, to obtain a high-performance lithium-rich manganese-based positive electrode material Li 1.2 Ni0.13 Co 0.13 Mn 0.54 O2.

[0035] Example 3

[0036] The difference from Example 1 is:

[0037] In step (2), 2 L of pure water is used as a medium, and 18 g of glucose is added into a sand mill for sand grinding;

[0038] In step (3), the inlet air temperature is 220°C and the outlet air temperature is 115°C.

[0039] Example 4

[0040] The difference from Example 2 is:

[0041] In step (1), NH3·H2O is used as a complexing agent with a concentration of 0.1 mol / L;

[0042] In step (2), 1 L of water was added as a medium and 10 g of sucrose was added and the mixture was put into a sand mill for sand grinding.

[0043] Example 5

[0044] The difference from Example 1 is:

[0045] In step (2), 1.6 L of pure water was used as a medium, and 4.8 g of CMC was added into a sand mill for sand grinding;

[0046] Comparative Example 1

[0047] (1) Weigh 19.755 g of Ni(OH)2, 19.806 g of Co(OH)2 (all purchased commercial Ni(OH)2 and Co(OH)2), 80 g of MnO2, and 82.532 g of LiOH·H2O, add 2 L of pure water as a medium, and add 28 g of sucrose, put them into a sand mill for sand grinding to obtain a slurry;

[0048] (2) adding the slurry obtained in step (1) into a spray dryer through a peristaltic pump for spray drying, wherein the inlet air temperature of the spray drying is 240° C., the outlet air temperature is 118° C., and the peristaltic pump speed is 18 rpm to obtain a solid powder;

[0049] (3) The powder of step (2) is placed in a box furnace for a two-stage calcination process. In the first step, the temperature is raised to 600°C and kept at this temperature for 3 h, and the heating time is 140 min; in the second step, the temperature is raised to 900°C and kept at this temperature for 3 h, and the heating time is 180 min, thereby obtaining a high-performance lithium-rich manganese-based positive electrode material Li 1.2 Ni0.13 Co 0.13 Mn 0.54 O2.

[0050] Comparative Example 2

[0051] The difference from Example 1 is:

[0052] The precursor, MnO2, and LiOH·H2O obtained in step (1) are directly sprayed without sand grinding, and then the positive electrode material Li is obtained under the same spraying and sintering conditions. 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2;

[0053] Comparative Example 3

[0054] (1) Weigh 461.8 g of Li2CO3, 462.5 g of MnO2, 98.9 g of CoO, 97.6 g of NiO and 9.3 g of WO3, add the raw materials and 2 L of pure water into a sand mill for sand grinding to obtain a slurry;

[0055] (2) adding the slurry obtained in step (1) into a spray dryer through a peristaltic pump for spray drying, wherein the inlet air temperature of the spray drying is 240° C., the outlet air temperature is 118° C., and the peristaltic pump speed is 18 rpm to obtain a solid powder;

[0056] (3) The powder of step (2) is placed in a box furnace for a two-stage calcination process. In the first step, the temperature is raised to 600 °C and kept at this temperature for 1 h, and the heating time is 140 min; in the second step, the temperature is raised to 900 °C and kept at this temperature for 2 h, and the heating time is 180 min, thereby obtaining a high-performance lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

[0057] Comparative Example 4

[0058] The difference from Example 1 is:

[0059] The mixed slurry obtained in step (3) is not spray-dried, but is dried in an oven and then ground, and then sintered under the same conditions to obtain a lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

[0060] Comparative Example 5

[0061] (1) Weigh a certain amount of NH3·H2O as a complexing agent, NaOH as a precipitant, and a mixture of CoSO4·7H2O, NiSO4·6H2O, and MnSO4 (molar ratio of 0.13:0.13:0.54) and dissolve them in pure water (concentrations of 0.6 mol / L -1 , 1.5 mol L -1 , 2 mol L -1 ), and then pumped into a continuous stirred tank reactor under nitrogen protection and stirring conditions. During the process, the temperature was maintained at 60 ° C, the pH value was maintained at 11.5, and the rotation speed was 350 rpm / min. After the reaction, the material was collected and filtered, washed, and dried to obtain Ni with a particle size D50 of 8.5 microns. 0.325 Co 0.325 Mn 1.35 (OH)2 precursor;

[0062] 30 g of the precursor powder of step (1) and 26.8 g of LiOH·H2O solid (4% excess to offset the loss of Li during sintering) were mixed and ground thoroughly, and then placed in a box furnace for a two-stage calcination process. In the first step, the temperature was raised to 600 °C and kept at this temperature for 1 h, and the heating time was 140 min; in the second step, the temperature was raised to 900 °C and kept at this temperature for 2 h, and the heating time was 180 min, to obtain a high-performance lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

[0063] Comparative Example 6

[0064] The difference from Example 1 is:

[0065] (2) 2 L of pure water was used as the medium without adding other carbon sources and placed in a sand mill for sand grinding.

[0066] The present invention tests the positive electrode materials prepared in the above embodiments and comparative examples for the tap density, capacity and cycle performance and the test results are shown in Table 1:

[0067] Table 1

[0068]

[0069] It can be seen from the above embodiments that the present invention provides a method for preparing a lithium-rich manganese-based positive electrode material, comprising the following steps: co-precipitating a nickel-cobalt mixed salt solution, a precipitant and a complexing agent to obtain a nickel-cobalt source; mixing the nickel-cobalt source, manganese source, lithium source, carbon source and water, and sand-milling to obtain a sand-milled slurry; spray-drying the sand-milled slurry to obtain a precursor; pre-calcining and sintering the precursor to obtain a lithium-rich manganese-based positive electrode material. The lithium-rich manganese-based positive electrode material prepared under the innovative process of co-precipitation-sand milling-spraying and the introduction of a carbon source has a high tap density, high capacity and high cycle performance. Experimental results show that the tap density of the lithium-rich manganese-based positive electrode material is 1.91~1.98g / cm 3 The first coulombic efficiency was 91.5~94.2%, the capacity retention rate after 200 cycles was 93.9~96.1%, and the 1C / 0.1C ratio was 83.6~85.7%.

[0070] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a lithium-rich manganese-based positive electrode material, comprising the following steps: The nickel-cobalt mixed salt solution, the precipitant and the complexing agent are subjected to co-precipitation reaction to obtain a nickel-cobalt source; The nickel-cobalt source, manganese source, lithium source, carbon source and water are mixed and sand-milled to obtain sand-milled slurry; spray drying the sand-milled slurry to obtain a precursor; Pre-calcining and sintering the precursor to obtain a lithium-rich manganese-based positive electrode material; The salt in the nickel-cobalt mixed salt solution is selected from one or more of sulfate, nitrate and acetate; The molar ratio of nickel to cobalt is 1:0-1.4; The concentration of nickel ions in the nickel-cobalt mixed salt solution is 1~2 mol / L; The concentration of cobalt ions in the nickel-cobalt mixed salt solution is 1~2 mol / L; The temperature of the coprecipitation reaction is 40~70℃; The particle size D50 of the nickel-cobalt source is 3 to 10 microns, and the reaction is stopped when the target particle size is reached.

2. The preparation method according to claim 1, characterized in that: The pH value of the sand-milling slurry is 8.6-13, the sand-milling temperature is 40-60° C., the sand-milling time is 0.5-24 h, and the sand-milling speed is 1000-3000 rpm.

3. The preparation method according to claim 1, characterized in that: The manganese source is selected from one or more of manganese dioxide, manganese trioxide, manganese tetraoxide, manganese chloride, manganese acetate, and manganese sulfate; The lithium source is selected from one or more of lithium hydroxide, lithium carbonate, lithium acetate and lithium nitrate; The total solid content of the sand grinding slurry is 5-50%; The carbon source is selected from one or more of glucose, sucrose and starch; the concentration of the carbon source in the sand-grinding slurry is 0.01-0.8 mol / L.

4. The preparation method according to claim 1, characterized in that: The inlet air temperature of spray drying is 150~500℃, the outlet air temperature is 80~150℃, and the peristaltic pump speed is 15~25rpm.

5. The preparation method according to claim 1, characterized in that: The pre-burning temperature is 450-700° C., the heating rate is 1-20° C. / min, and the heat preservation time is 0.5-24 h.

6. The preparation method according to claim 1, characterized in that: The sintering temperature is 750~1100℃, the heating rate is 1~20℃ / min, and the holding time is 0.5~24h.

7. The preparation method according to claim 1, characterized in that: The composition of lithium-rich manganese-based positive electrode materials is Li x Ni y Co z Mn t O2, where x is 0.9~1.4, y is 0.11~0.29, z is 0.11~0.29, and t is 0.51~0.

58.

8. The preparation method according to claim 1, characterized in that: The precipitant is sodium hydroxide solution or sodium carbonate solution, and the concentration of the precipitant is 0.1~2mol / L; The complexing agent is ammonia water or NH4·HCO3.

Citation Information

Patent Citations

  • Manganese-iron atomic-scale mixed lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN118723960A